Long‐term follow‐up of patients undergoing standardized bicycle exercise stress testing: new recommendations for grading of exercise capacity are clinically relevant. (27th November 2019) - Lindow, Thomas; Brudin, Lars; Elmberg, Viktor; Ekström, Magnus
Summary: Introduction: A new grading of exercise capacity during bicycle stress testing has been proposed in Sweden based on the new reference material ('the Kalmar material'), which has not been validated. We aimed to examine the prognostic information of the new grading of exercise capacity during exercise stress testing. Methods: Data on all bicycle exercise tests performed at the Department of Clinical Physiology in Kalmar between May 2005 and October 2016 were cross‐linked with the Causes of Death Register (until 30 April 2019) and the National Patient Register (until 12 December 2017). Exercise capacity was graded based on predicted exercise capacity: ≥120% (good), 75 to <120% (normal), 70 to <75% (mildly reduced), 50 to <70% (moderately reduced) and <50% (severely reduced). Associations with all‐cause mortality, cardiovascular mortality and hospitalization for ischaemic heart disease (IHD) and heart failure were analysed using Cox regression. Results: A total of 13 887 patients were followed a median of 7·7 years (interquartile range 5·0–10·8); 1809 patients died (546 from cardiovascular disease). Compared to normal exercise capacity, reduction of exercise capacity was strongly associated with increased all‐cause mortality [(hazard ratio; 95% confidence interval): mild (3·0; 2·6–3·5); moderate (4·4; 3·9–4·9); and severe reduction (8·5; 7·2–10·0)]. Reduced exercise capacity was also associated with increased risks of cardiovascular hospitalization and mortality. Conclusion: Reduced exercise capacity is associated with increased all‐cause and cardiovascular mortality, as well as increased risk of future IHD and heart failure diagnosis and hospitalization. In patients with reduced exercise capacity, mortality is progressively increased with worsening grade of exercise capacity.